REVOLUTIONIZING OTONEUROLOGY: A COMPREHENSIVE REVIEW OF ADVANCED DIAGNOSTIC TECHNIQUES AND THEIR LONG-TERM IMPACT ON PATIENT CARE - Koch, Everson Dias; Vilela, Lázaro Felipe Costa; Destefani, Afrânio Côgo; Destefani, Vinícius Côgo (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2024)
Otoneurology, a field at the intersection of otolaryngology and neurology, has evolved significantly in diagnostic techniques over the last decade. Recent advancements, including advanced imaging, genetic testing, and artificial intelligence, have enhanced the precision of diagnosing auditory and vestibular disorders. This review highlights the transformative impact of these methodologies on patient care, emphasizing the importance of accurate early diagnosis in improving quality of life. By addressing limitations of traditional approaches, these innovative techniques provide deeper insights into the complexities of inner ear and neural function, paving the way for personalized treatment strategies.